De verdwenen kloosterkerk van Wittewierum (Groningen). Gebouw en inrichting tussen late middeleeuwen en vroegmoderne tijd - Kroesen, Justin (Jaarboek voor liturgieonderzoek, 2010)
Although little remains of the premonstratensian monastery of Bloemhof in Wittewierum, east of the city of Groningen (Netherlands), this abbey became immortal by the unique medieval chronicle written by the abbots Emo and Menko. To some detail this chronicle describes when and how the church was built and how it was furnished. Important aspects of this description were confirmed in 2001, during excavations by Jan Battjes and Hans Ladrak. Reconstruction shows that the church was a three-aisled basilica with arcades following the so-called ‘alternating system’ and a tripartite eastern end consisting of three apses. We are informed about the church’s furnishings in the late Middle Ages by a description dating from 1632 which affirms the rights of the noble families Tuinga and Rengers. This description is more or less contemporaneous with three unique sketched ground-plans which not only provide outlines of the building but also indicate where the most important parts of the furnishings were situated. Together, these sources offer unique insights into the architecture and furnishings of a Groningen abbey church right after its foundation and on the eve of the Reformation, as well as into the sweeping changes that occurred after the arrival of Protestantism. In a broader cultural sense, the case of Wittewierum shows us how church space evolved from a stage for the liturgical ritual into a best room which was adopted by the elites to display personal or collective prestige.